Depth and Dimension: Exploring the Problems and Potential of Photogrammetric Models for Ancient Coins. Issue 1 (1st September 2022) - Morris, Gala; Emmitt, Joshua; Armstrong, Jeremy
In numismatic collections, coins are typically documented and studied using 2D images of their obverse and reverse. While two photographs, under the correct lighting, provide adequate information for basic research, detailed numismatic study has generally required the physical handling of the items to capture the three-dimensional aspects of the coin. Recent advances in photogrammetry and digitisation provide new opportunities for numismatic research. Digitised, 3D models of ancient coins allow researchers and students to interact with these coins remotely, providing opportunities to study coins from collections that would otherwise be difficult to access. Ancient coins, however, can be challenging to digitise due to their small size, irregular shape, and reflectance. This study will explore and outline a methodology for creating 3D models of ancient coins that balances both expediency with quality. Three Roman Republican coins from the University of Auckland's numismatic collection were digitised using photogrammetric methods to create 3D digital models for student use. Expedient capture relied primarily on the quality of the photogrammetry setup, as well as the use of macrophotography, to capture the detail of each coin effectively. While the digital models took longer to produce than traditional 2D images, it was possible to create high-quality digital 3D model coins in a relatively expedient manner. The balance between speed and increased data opens the door for a new era in numismatic cataloguing and qualitative research opportunities.